Effects of Organic-Based and Foliar Fertilizers on the Growth, Yield and Quality of Cocoa (Theobroma Cacao L.) - Nordin, Noordiana (2007)
Malaysian cocoa industries are facing many problems when cocoa in the country is grown on problem soils such as Ultisols and Oxisols. These soils are generally acidic, low in basic cations and also low in soil cation exchange capacity. Poor cocoa yield that was far behind the targeted yield of 1.5 tonnes contribute to reducing in Malaysian cocoa export. A combination of chemical and organic fertilizers have been shown to maintained the physical, chemical and biological of soil despite maximizing continuous production. Foliar fertilizer reduces the imbalance nutrients condition during critical growing stages. The general objective of this study was to evaluate the effect of different types of fertilizers on the cocoa growth production and the quality of cocoa beans. Thus, the specific objectives of this study were to see the effects of fertilizer treatments (organic-based and foliar fertilizers) on (i) soil fertility improvement; (ii) the growth of (matured tree and seedlings) and (iii) yield and beans quality of cocoa grown on Segamat Series. A field experiment was undertook to study the effects of organic-based and foliar fertilizers on the soil fertility improvement, the growth, yield and beans quality of cocoa grown on Segamat series. Experimental plots were prepared in Malaysian Cocoa Board (MCB) Experimental Farm with five treatments and four replications. The number of pods (successful cherelles) was recorded every month, starting 2 months after treatments. Total number of harvested mature pods was recorded from October 2004 until June 2005. The potential calculated yield was then estimated using the collected data of number of pods (successful cherelles) and harvested pods. Five pods were sampled out from each plot to determine pod and bean quality indicated by dry weight of husk, length and diameter of pods, weight of harvested pods, average number of beans/pod, single dry bean weight and pod index. A pot experiment was conducted under glasshouse conditions using cocoa seedlings of clone KKM 22 and PBC 130 grown in Segamat Series soil with five treatments. The experiment was conducted to determine the effect of organic-based and foliar fertilizers (as measured by plant height, stem diameter, and weight of root and top) on the growth of cocoa seedlings. The experiment was conducted for 20 weeks starting in August 2005 until January 2006. Root:shoot ratio and plant height showed no significant response to treatments except the stem diameter, root biomass and shoot (plant top) dry weight. Results showed that application of fertilizers gave no significant difference on the growth, yield or quality of cocoa. Therefore, further soil and leaf analysis had been carried out to identify the actual problem of yield limitation by determining the concentration of macro- and micronutrients. It was discovered that manganese concentrations in soil and leaf samples for field experiment were 3-fold higher than the adequate range, possibly resulting in manganese toxicity, therefore cocoa was not grown on good soil. Manganese toxicity has been found out to be the possible reason of cocoa yield and quality limitation. The Segamat series contains mineral such as pyroxene which contributes to Mn. Initial status of Segamat series soil has indicated that Mn concentration was 113 – 150 mg/kg, which were beyond the adequate range of 20 – 40 mg/kg. An addition of Mn through fertilizer application has made the problem worst. It is recommended that enough lime should be applied to the soil since the present liming program (500 g/plant or 0.5 – 1 tan/ha/year, broadcast once a year) has indicated insufficient to increase the soil pH to an adequate range of 5.5 – 7.0 in order to obtain better yield and quality of cocoa grown on Segamat series soil.